Campus Security Measures and Perceived Undergraduate Satisfaction in Obafemi Awolowo University, Ile-Ife, Nigeria - Ajadi, Olugbenga (COMPETITIVE: Journal of Education, 2025)
Students are considered an important component of the university.  In fact, without them, existence of a university may be a mirage.  However, undergraduates expressed dissatisfaction with the state of electricity, security patrol vehicles, unavailability of close circuit television and other safety devises in Nigerian universities.  As a result, this study investigated Campus Security Measures and Perceived Undergraduate Satisfaction in Obafemi Awolowo University (OAU), Ile-Ife, Nigeria.  The study population comprised undergraduates from the 10 Faculties and one College in OAU.  A sample size of 300 was selected for the study.  A self-designed questionnaire titled ‘Campus Security and Undergraduate Satisfaction Questionnaire (CSUSQ) was used to collect with reliability index of 0.83.  Two research questions were raised and answered and one hypothesis tested by the study.  The study found that the perception of OAU undergraduates on effectiveness of campus security measures was very high, and the effectiveness of security measures in place by OAU administration was high.  In addition, the study revealed a significant composite influence of the campus security measures on undergraduate satisfaction.  It was recommended that the university administration need to improve in providing more security facilities that will guarantee student satisfaction on campus.